PENGEMBANGAN DESAIN LEMBAR KERJA PESERTA DIDIK (LKPD) BERMUATAN NILAI PENDIDIKAN KARAKTER PADA PEMBELAJARAN TEKS FABEL KELAS VII DI SMPN 2 PUGUNG TANGGAMUS - Fadira, Laudya; Widodo, Mulyanto; Meirita, Siska (Universitas Lampung, 2022)
The problem in this research is how the development and feasibility of the LKPD design contains the value of character education in learning fable texts in class VII SMP. The purpose of this study, namely to describe and evaluate the results of the development of the LKPD design containing the value of character education in learning fable texts for class VII SMP. This research uses research and development (R&D) methods. The results of this study, namely the creation of a LKPD design containing the value of character education in learning fable texts for class VII that has been validated. Validation is carried out by the lecturer as a material expert to test the feasibility of the LKPD design. Based on the results of the feasibility assessment of teaching materials obtained from material experts, an average value of 3.14 was obtained which was classified as